The Rostock International Parkinson's Disease (ROPAD) Study: Protocol and Initial Findings. Issue 4 (14th December 2020) - Skrahina, Volha; Gaber, Hanaa; Vollstedt, Eva‐Juliane; Förster, Toni M.; Usnich, Tatiana; Curado, Filipa; Brüggemann, Norbert; Paul, Jefri; Bogdanovic, Xenia; Zülbahar, Selen; Olmedillas, Maria; Skobalj, Snezana; et al.
ABSTRACT: Background: Genetic stratification of Parkinson's disease (PD) patients facilitates gene‐tailored research studies and clinical trials. The objective of this study was to describe the design of and the initial data from the Rostock International Parkinson's Disease (ROPAD) study, an epidemiological observational study aiming to genetically characterize ~10, 000 participants. Methods: Recruitment criteria included (1) clinical diagnosis of PD, (2) relative of participant with a reportable LRRK2 variant, or (3) North African Berber or Ashkenazi Jew. DNA analysis involved up to 3 successive steps: (1) variant ( LRRK2 ) and gene ( GBA ) screening, (2) panel sequencing of 68 PD‐linked genes, and (3) genome sequencing. Results: Initial data based on the first 1360 participants indicated that the ROPAD enrollment strategy revealed a genetic diagnostic yield of ~14% among a PD cohort from tertiary referral centers. Conclusions: The ROPAD screening protocol is feasible for high‐throughput genetic characterization of PD participants and subsequent prioritization for gene‐focused research efforts and clinical trials. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.